Long-term performance of cochlear implants in postlingually deafened adults - Lenarz, Minoo; Sönmez, Hasibe; Joseph, Gert; Büchner, Andreas; Lenarz, Thomas (Otolaryngology-head and neck surgery, 2012)
To evaluate the stability of long-term hearing performance after cochlear implantation (CI) in postlingually deafened adults and to explore the boundaries and limitations of the present test batteries for adult CI patients. Case series with chart review. Tertiary referral center. A cohort of 1005 postlingually deafened adult cochlear implantees, who received their implants after age 18 years, was unilaterally implanted and had no inner ear malformations or cochlear ossification. Hearing performance with cochlear implant was evaluated with the help of 5 standard German speech tests. The average performance improved significantly during the first 6 months in all tests (learning phase) and afterward entered a plateau phase in which no statistically significant improvements or deteriorations were observed for more than 20 years of follow-up. For each test, the average performance of the cohort, the ceiling effect, and the average results for high and low performers are presented. In this study, postlingually deafened adults required about 6 months to learn how to process the artificial signals delivered by the cochlear implant. After this learning phase, the hearing performance entered a stable plateau phase for more than 20 years. This stability reveals the long-term reliability of the technology and the biological stability of the electrode-nerve interface over years. In this study, the authors also evaluated the "ceiling effect" with 5 standard German speech tests, used for evaluation of postlingually deafened adult CI patients.